Excessive Activation of Notch Signaling in Macrophages Promote Kidney Inflammation, Fibrosis, and Necroptosis - Ma, Tiankui; Li, Xin; Zhu, Yonghong; Yu, Shufan; Liu, Tianyan; Zhang, Xiaodan; Chen, Dong; Du, Shuyan; Chen, Tong; Chen, Shuo; Xu, Yanyan; Fan, Qiuling (Frontiers in Immunology, 2022)
Diabetic nephropathy (DN) is one of the main causes of end-stage renal disease (ESRD). Existing treatments cannot control the progression of diabetic nephropathy very well. In diabetic nephropathy, Many monocytes and macrophages infiltrate kidney tissue. However, the role of these cells in the pathogenesis of diabetic nephropathy has not been fully elucidated. Here, we analyzed patient kidney biopsy specimens, diabetic nephropathy model animals. Meanwhile, we cocultured cells and found that in diabetic nephropathy, damaged intrinsic renal cells (glomerular mesangial cells and renal tubular epithelial cells) recruited monocytes/macrophages to the area of tissue damage to defend against and clear cell damage. This process often involved the activation of different types of macrophages. Interestingly, the infiltrating macrophages were mainly M1 (CD68+iNOS+) macrophages. In diabetic nephropathy, crosstalk between the Notch pathway and NF-κB signaling in macrophages contributed to the polarization of macrophages. Hyperpolarized macrophages secreted large amounts of inflammatory cytokines and exacerbated the inflammatory response, extracellular matrix secretion, fibrosis, and necroptosis of intrinsic kidney cells. Additionally, macrophage depletion therapy with clodronate liposomes and inhibition of the Notch pathway in macrophages alleviated the pathological changes in kidney cells. This study provides new information regarding diabetic nephropathy-related renal inflammation, the causes of macrophage polarization, and therapeutic targets for diabetic nephropathy.